The Effect of Materiality Principle Adoption on Financial Accountability of State Corporations in Nakuru City, Kenya - Papa, Nabwire Mercy; Kamau, John Gathii; Tallam, Zakayo (Kabarak University, 2024)
Abstract State corporations play a crucial role in Kenya's socioeconomic development. To fulfill their mandates and deliver value to taxpayers, these entities must uphold strong financial accountability. The State Corporations Act of 2012 outlines several key requirements to ensure financial accountability. State corporations face many accountability challenges when presenting financial statements. Accounting standards aim to improve the quality and comparability of financial reporting in the public sector. This study looks at the effect of materiality principle adoption on the financial accountability of state corporations in Nakuru City. This study adopted a quantitative, cross-sectional research design grounded in agency theory and financial accounting theory. The target population comprised senior administrative and finance/accounting staff from 12 selected state corporations in Nakuru City. A structured questionnaire was administered to a sample of 58 individuals from these corporations. A correlation was found between the materiality principle adoption and financial accountability. A linear regression analysis was conducted to examine the extent of the relationship between the materiality principle adoption and financial accountability. Respondents generally disagreed that financial statements always lack misstatements, indicating recognition of potential errors. Based on the evidence from the correlation analysis, linear regression, and ANOVA, the null hypothesis (H₀) was rejected. This indicates a statistically significant relationship between the materiality principle adoption and financial accountability in state corporations in Nakuru City. Adhering to the materiality principle can have a positive impact on improving financial accountability within these organizations.
Full text
Keywords: Materiality Principle; Financial Accountability; State Corporations